The relationship of routine exercise and body mass index to dysmenorrhea severity among young women - W Wahyuni; Nor Azlin Mohd Nordin; M Mutalazimah (Universitas Udayana dan Diaspora Taipei Medical University, 2025)
Background: There are several risk factors for dysmenorrhea, including high body mass index (BMI) and lack of exercises. The study's goal was to determine the relationship between routine exercises and body mass index with the levels of primary dysmenorrhea pain in young women. Methods: This study was conducted among 514 young women in Surakarta used a cross-sectional design. Inclusion criteria were females aged 15–24 years with regular menstruation and no use of medications affecting the menstrual cycle, while exclusion criteria included a history of reproductive organ surgery, ongoing treatments affecting the cycle, or abnormal uterine bleeding. This study used questionnaires developed by the researcher to collect patients’ characteristics, pain level, and frequency of exercise data. Data were analyzed using the Chi-Square Test. Results: The majority of respondents were aged 17–18 years, experienced menarche at 12–14 years, had normal BMI, and reported primary dysmenorrhea with moderate pain intensity. The Chi-square test between routine exercises and degrees of dysmenorrhea showed a value of p-value < 0.001, and between BMI and degrees of dysmenorrhea showed a value of p-value = 0.537, where the results of the Chi-square test was different between them. The routine exercise was related to the levels of primary dysmenorrhea pain, but the BMI was not related to the levels of primary dysmenorrhea pain. Conclusion: There was a significant relationship between routine exercises with the degrees of primary dysmenorrhea pain, but no significant relationship was found between BMI and degrees of primary dysmenorrhea pain.